Effect of film thickness and temperature on the resistive switching characteristics of the Pt/HfO2/Al2O3/TiN structure. (November 2020) - Liu, Yulin; Ouyang, Sha; Yang, Jie; Tang, Minghua; Wang, Wei; Li, Gang; Zou, Zhi; Liang, Yifan; Li, Yucheng; Xiao, Yongguang; Yan, Shaoan; Chen, Qilai; et al.
Highlights: This study explored the influence of thickness and temperature on the electrical properties of Pt / HfO2 / Al2 O3 / TiN structure RRAM devices. Adjust the performance of the device by adjusting the thickness of the double-layer film. The results obtained have important guiding significance for one-step experimental application. Abstract: Thin films with HfO2 /Al2 O3 laminated structure were prepared by the ALD method in this paper. Typical bipolar resistance switching characteristics were observed in the Pt/HfO2 /Al2 O3 /TiN structure device. The samples were characterized by X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM). The effects of dielectric thickness and different test temperatures on the electrical performance were investigated. Experiments show that when the thickness of HfO2 /Al2 O3 is 7 nm/3 nm, the electrical properties are the best. As the test temperature increases, the resistance values ( R LRS and R HRS ) of the Pt/HfO2 /Al2 O3 /TiN structure fluctuate more and more. When the test temperature approaches the failure temperature, the device's transition voltages ( V Set and V Reset ) will also become more volatile.